Dual higher education study or advanced training - what increases the chances of career advancement? - Maier, Tobias [Verfasser]; Steeg, Stefanie [Verfasser] (My University, 2019)
"Although the number of graduates with a bachelor’s degree has risen over recent years, little information is available as to which position such persons assume within a firm and especially with regard to whether they vie for company advancement with those in possession of the formally equivalent qualifications of master craftsman, technician or certified senior clerk. This article presents the results of a company survey, which uses a choice experiment to identify possible competition for appointment to project management positions between persons who have completed advanced training and bachelor’s programmes graduates (dual course of study)." (Author's abstract ; BIBB-Doku)
Duales Studium oder Fortbildung - Was erhöht die Chancen für einen betrieblichen Aufstieg?
Keywords: S 1.4 Hochschulbildung; S 3.2 Unternehmen und Behörden; G 2.4.1 Bildungs- und Berufswege; Dualer Studiengang; Bachelor; Aufstiegsfortbildung; Absolvent; Betrieb; Beruflicher Aufstieg; Wettbewerb; Betriebsbefragung; Referenzbetriebssystem